Strategi Penyediaan Pendidik dan Tenaga Kependidikan pada Lembaga Pendidikan Islam - Jaelani Anton Pratama Putra; Fitria Rosmi; Rama Nursyinsyah; Iswan (STKIP Subang, 2026)
This study aims to analyze strategies for the provision of educators and educational personnel in Islamic educational institutions. The study was conducted to address the numerous issues related to educators and educational personnel whose qualifications are inadequate or whose job responsibilities do not align with their competencies and skills. This research employed a qualitative approach using a library research method. The findings indicate that strategic management is essential in the provision of educators and educational personnel to improve the quality of Islamic educational institutions. Such strategic management includes structured and systematic processes of planning, recruitment, placement, and professional development of educators and educational personnel.